From German Studies to the Job Market – Review and Present State (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
Professional positioning of prospective graduates of German philology on the contemporary job market has been the main subject of numerous discussion panels, conferences and articles. On the one hand, the issue of current social relevance of German studies and their possible textual focus on other, traditionally well-established, subjects (literature and linguistics), e.g. specialised communication, specialised training, specialised translation and interpreting, is the centre of attention. On the other hand, it is the question of competence orientation of graduates of German philology that comes into play. It is understood as linguistic and specialised competences as well as key competences, both intercultural and rhetoric, which are currently in high demand. The present study attempts at investigating such questions and providing a systematic overview of the most important problems in a given context based on a number of exemplarily selected publications.